Агаарын геофизикийн судалгааны ажлын эдийн засгийн урьдчилсан тооцоо - З.Ганбаатар; Э.Ганхүү (Geological Issues, 2023)
There is still unexplored areas left in total surface of Mongolia by airborne geophysical survey. In today’s world, the necessity of airborne geophysical survey is increasing; Mongolian experts are in search of opportunities to explore the total surface area of the country using technological advances. Time frame required for research and cost analysis in comparison with other similar project are discussed in this article.